Expression of scorpion toxin LqhIT2 increases the virulence of Metarhizium acridum towards Locusta migratoria manilensis. (1st November 2014) - Peng, Guoxiong; Xia, Yuxian
Abstract: LqhIT2 is an insect-specific neurotoxin from the venom of scorpion. In this study, the LqhIT2 gene was introduced into the entomopathogenic fungus, Metarhizium acridum . The virulence of the genetically modified strain MaLqhIT2 was then evaluated against locusts ( Locusta migratoria manilensis ). Compared with the wild-type strain, the median lethal cell density (LC50 ) for MaLqhIT2 was a 22.6-fold lower, and the median times to death (LT50 ) for MaLqhIT2 were reduced by 30.3 and 29.6 %, respectively, after topical inoculation and injection. MaLqhIT2 also grew significantly faster in the hemolymph than wild-type strain. There were no significant differences in germination, appressorium formation and sporulation in locust carcasses between the MaLqhIT2 and wild-type strain. These results indicate that LqhIT2 increased the virulence of M. acridum towards locusts by shortening the in vivo infection period, without affecting cuticle penetration or conidia formation in the carcasses. LqhIT2 thus shows considerable potential for increasing fungal virulence against locusts.